Identifikasi Strategi dan Faktor Keberhasilan Perusahaan Startup: Studi Kasus Perusahaan Startup Makanan dan Minuman di Indonesia - Anindhita, Yusi; Dede, Agustin; Agus, Agus (Proceeding Mercu Buana Conference on Industrial Engineering, 2021)
Every company experiences life cycle stages, where this cycle is identical to the Company's life cycle. There are 5 phases in the company's life cycle, namely the establishment or startup stage, the expansion stage, the maturity stage, and the declining stage. Startup Companies are companies that are in the early stages of operating and developing or have not yet operated. One promising startup sector is a food and beverage company startup. Food and beverage-based startup companies are one of the sectors most targeted by investors even though the global economy is being pressured by the coronavirus outbreak. One of the crucial problems for startup companies is business strategy, this is because startup companies have different characteristics from mature companies such as in decision-making. There are many factors that influence the success of a startup company. Therefore the purpose of this study is to identify the strategies used by food and beverage startup companies and determine the most influential factors in the success of the startup. This research was conducted by structurally interviewing 22 startup companies, then processing the data using AHP (analytical hierarchical process) in determining the level of the most influential success factors. The results show that the most widely used strategy is market penetration of 68% and the level of the factor that has the highest influence on success is the individual factor group of 5,111